Q. 83.6( 14 Votes )

v<span lang=

Answer :

By splitting the middle term


v2 + 4√3 v - 15 = 0


v2 + (5√3v - 3√3v) - 15 = 0


v2 + 5√3v - 3√3v - 15 = 0


v (v + 5√3) - √3(v + 5√3) = 0


(v + 5√3)(v - √3) = 0


v = - 5√3, √3


Verification:


Sum of the zeroes = - (coefficient of x) ÷ coefficient of x2


α + β = - b/a


(- 5√3) + (√3) = - 4√3


= - 4√3 = - 4√3


Product of the zeroes = constant term ÷ coefficient of x2


α β = c/a


(- 5√3)(√3) = - 15


- 15 = - 15


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses